Artistic sports activities effectiveness for enhancing students’ academic performance among left-behind children: mediating effects of loneliness - Zhou, Yutao; Ferraro, Francesco Vincenzo; Fan, Chengwen (Frontiers in Psychology, 2024)
Abstract Introduction: Numerous studies within the school and academic contexts have underscored the profound impact of psychometric variables such as academic self-efficacy, self-esteem, and loneliness on academic achievement among children. Although physical activities and dance practices are known to bolster academic self-efficacy and enhance academic outcomes, the effect of Artistic Sports Activities on these psychological determinants among left-behind children (LBC) in rural schools remains underexplored. Method: This study was conducted from September 2020 to January 2022 among 405 LBCs aged 9 to 13 from six randomly selected primary schools in Hunan Province, China. Schools were chosen in collaboration with the Hunan Women and Children's Federation, ensuring informed consent through stakeholder informational sessions. The study employed rigorous sampling and data analysis methods, including the Shapiro-Wilk test for normal distribution and Cronbach's alpha for reliability, alongside Pearson correlation, independent and paired t-tests, and multiple linear regression analyses to investigate the effects of Artistic Sports Activities on psychometric variables and academic performance among LBCs. Data collection involved standardised questionnaires assessing academic self-efficacy, self-esteem, and loneliness before and after intervention. Results: Findings indicate that Artistic Sports Activities significantly improved academic self-efficacy and self-esteem and reduced loneliness, leading to enhanced academic performance. Notably, loneliness was identified as mediating the relationship between academic self-efficacy and self-esteem among LBCs. Discussion: The findings highlight the critical role of integrating Artistic Sports Activities in educational frameworks to bolster psychological and academic outcomes for LBCs. The study reveals the intricate interplay between loneliness, self-esteem, and academic self-efficacy, underscoring the necessity for targeted educational interventions.